GE_GERICHTE C/21033/2011 vom 25. September 2013 - GE Cour de justice (2013)
COURTAGE; CONCLUSION DU CONTRAT; HONORAIRES; DÉPENS | CO.18; CO.412.1; CO.413.1; CC.8; CPC.95; CPC.105.1; LaCC.23.1; RTFMC.84; RTFMC.85